2021
DOI: 10.1002/adhm.202101606
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Generated Using Bioreactors and their Therapeutic Effect on the Acute Kidney Injury Model

Abstract: Extracellular vesicles (EVs) are nano-sized vesicles secreted by cells, having beneficial effects for various types of regenerative processes. Although EVs have shown promising effects as therapeutic agents, these effects are difficult to research due to the limitations of EV production. In this study, an EV production method based on a flat-plate bioreactor is introduced. The bioreactor produces approximately seven times more mesenchymal stem cell-derived EVs than static culture conditions. The mechanism unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Coupled with our data, this could mean that the increased EV production we observed in this bioreactor system is a result of fluid dynamics rather than a specific mechanoresponse of the cells. However, in a recent study, while culturing MSCs in a flat-plate perfusion bioreactor, Kang et al found that flow increased intracellular calcium as well as calcium-related proteins, and thus could be a mechanism behind the increase in EV biogenesis [14]. Separately, Guo and colleagues found that the increased MSC EV production present within their perfusion bioreactor was dependent on the expression of yes-associated protein (YAP), a well-known cellular mechanotransducer [12, 56, 57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coupled with our data, this could mean that the increased EV production we observed in this bioreactor system is a result of fluid dynamics rather than a specific mechanoresponse of the cells. However, in a recent study, while culturing MSCs in a flat-plate perfusion bioreactor, Kang et al found that flow increased intracellular calcium as well as calcium-related proteins, and thus could be a mechanism behind the increase in EV biogenesis [14]. Separately, Guo and colleagues found that the increased MSC EV production present within their perfusion bioreactor was dependent on the expression of yes-associated protein (YAP), a well-known cellular mechanotransducer [12, 56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…Of the various therapeutic applications of MSCs and MSC EVs elucidated thus far, the role they play in tissue reparative processes (e.g., angiogenesis) has been well-documented [58][59][60][61]. Moreover, it is known that flow-derived shear stress can be used to influence the regenerative properties of both MSCs and their secreted EVs [14]. Across two orthogonal angiogenic assays (i.e., cell migration and tube formation), we found that the angiogenic properties of MSC EVs derived from the perfusion bioreactor were at least as effective as those from flask-grown MSCs (Figure 4B, C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, bioreactorbased culture allows for the implementation of physiological parameters, including flow-derived shear stress, and has been shown to significantly increase EV production across numerous studies [5][6][7][8][9][10][11][12][13][14]. Importantly, the shift from static to dynamic culture is also known to cause dramatic changes in the EV therapeutic profile [9,12,[14][15][16]; in some cases elucidating EV effects that were not present when utilizing traditional flask culture [15]. This phenomenon of altered EV bioactivity can also be observed when implementing different EV isolation strategies such as tangential flow filtration (TFF), ultracentrifugation (UC), or size-exclusion chromatography (SEC) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of EV production, there has been a collective movement to implement dynamic and/or 3D cell culture microenvironments, as these techniques are often more scalable than traditional flask culture and can produce EVs that resemble those within the physiological niche [4]. Specifically, bioreactorbased culture allows for the implementation of physiological parameters, including flow-derived shear stress, and has been shown to significantly increase EV production across numerous studies [5][6][7][8][9][10][11][12][13][14]. Importantly, the shift from static to dynamic culture is also known to cause dramatic changes in the EV therapeutic profile [9,12,[14][15][16]; in some cases elucidating EV effects that were not present when utilizing traditional flask culture [15].…”
Section: Introductionmentioning
confidence: 99%